Two stories of cruelty. Epilogue to the second treatise of The Genealogy of Morals by F. Nietzsche - Castro Orellana, Rodrigo (Logos. Anales del Seminario de Metafísica, 2022)
This article presents an analysis of the second treatise in On the Genealogy of Morality, identifying two different approaches to the problem of cruelty. On the one hand, the treatise offers a transformational and affirmative perspective of suffering, and on the other, a reactive mode of confronting pain that leads to resentment toward life. These two points of view are expressed as two historical tales based on different references to Nietzsche’s works while paying close consideration to Deleuze’s reading. This analysis illustrates the process that made it possible for ideals hostile to life to triumph and the horizon of redemption that the German thinker unveils through his “great health” concept. The article concludes by sketching an outline of how these two ways of understanding cruelty and their anthropological foundations are present in contemporary political theory.